2013
DOI: 10.22401/jnus.16.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Detection of local Erwinia Isolates Causing Diseases in Potato by Using DNA Amplification by Polymerase Chain Reaction Technique (PCR)

Abstract: Seventy samples of infected potato's tubers were collected from Baghdad city during the period from September 2011 to February 2012. These samples were collected from Alradwaniyah potato's store/ Albyaa market and from Awrad Alnahar potato's store in Abu ghraib and two bacterial strains of Erwinia were obtained from Plant Protection department/ College of Agriculture/ Baghdad University. The Crystal Violet Pectate (CVP) used as a selective-diagnostic medium to isolate and purify Erwinia. The strains and isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…It was found that Pcc belonged to the Enterobacteriaceae family that possessed circular, creamy, convex, smooth and entire margin, gram-negative, rod-shaped, none forming spores, motile with peritrichous flagella and cannot produce pigments. They grow and form pits on CVP media, creamy colored colonies with no fluorescent pigment on King B medium and produce small and dark red colonies on raffinose medium, the results of the present study are in accordance with the finding obtained by (Kettani-Halabi et al, 2013 andMohamed &Selman, 2013). Biochemical tests on Pcc isolates gave positive reactions for KOH, pectinase, catalase, methyl red, voges proskaur, casein and gelatin hydrolysis, H2S production, Citrate and acid production from glucose, sucrose, fructose, lactose, cellobiose and raffinose tests.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was found that Pcc belonged to the Enterobacteriaceae family that possessed circular, creamy, convex, smooth and entire margin, gram-negative, rod-shaped, none forming spores, motile with peritrichous flagella and cannot produce pigments. They grow and form pits on CVP media, creamy colored colonies with no fluorescent pigment on King B medium and produce small and dark red colonies on raffinose medium, the results of the present study are in accordance with the finding obtained by (Kettani-Halabi et al, 2013 andMohamed &Selman, 2013). Biochemical tests on Pcc isolates gave positive reactions for KOH, pectinase, catalase, methyl red, voges proskaur, casein and gelatin hydrolysis, H2S production, Citrate and acid production from glucose, sucrose, fructose, lactose, cellobiose and raffinose tests.…”
Section: Discussionsupporting
confidence: 93%
“…Biochemical tests on Pcc isolates gave positive reactions for KOH, pectinase, catalase, methyl red, voges proskaur, casein and gelatin hydrolysis, H2S production, Citrate and acid production from glucose, sucrose, fructose, lactose, cellobiose and raffinose tests. Conversely, all Pcc isolates can grow at 37°C, 5% and 7% NaCl, but all isolates gave negative reactions for oxidase, indole, urease, starch hydrolysis, and acid production from maltose tests these results are compatible with (Mohamed andSelman, 2013 andNazerian et al, 2013). The biochemical results were confirmed by the API system that revealed that the tested isolates belong to Pectobacterium carotovorum, these results are compatible with (Mohamed andseleman, 2013 andHassan,2017).…”
Section: Discussionsupporting
confidence: 72%
“…Whereas control tubers were inoculated with distilled water rather than the bacterial suspension, and then all experiment tubers were kept at 28 °C ± 2 for 5 days. The size of the rotted areas created by each isolate on potato tubers was a significant indication of the rotting ability of the isolates [24].…”
Section: Pathogenicity Testmentioning
confidence: 99%
“…The damage to the potato slice was measured by measuring the diameter of the lesion. Isolates with high pathogenicity in the potato slice assay were selected and stored in sterile test tubes in the refrigerator for use in subsequent experiments [13][14][15][16][17].…”
Section: Testing the Pathogenicity Of Bacterial Isolates On Potato Tu...mentioning
confidence: 99%